Biological impact of iberdomide in patients with active systemic lupus erythematosus. Issue 8 (27th April 2022) - Lipsky, Peter E; Vollenhoven, Ronald van; Dörner, Thomas; Werth, Victoria P; Merrill, Joan T; Furie, Richard; Petronijevic, Milan; Velasco Zamora, Benito; Majdan, Maria; Irazoque-Palazuelos, Fedra; Terbrueggen, Robert; Delev, Nikolay; et al.
Abstract : Objectives: Iberdomide is a high-affinity cereblon ligand that promotes proteasomal degradation of transcription factors Ikaros ( IKZF1 ) and Aiolos ( IKZF3 ). Pharmacodynamics and pharmacokinetics of oral iberdomide were evaluated in a phase 2b study of patients with active systemic lupus erythematosus (SLE). Methods: Adults with autoantibody-positive SLE were randomised to placebo (n=83) or once daily iberdomide 0.15 mg (n=42), 0.3 mg (n=82) or 0.45 mg (n=81). Pharmacodynamic changes in whole blood leucocytes were measured by flow cytometry, regulatory T cells (Tregs) by epigenetic assay, plasma cytokines by ultrasensitive cytokine assay and gene expression by Modular Immune Profiling. Results: Iberdomide exhibited linear pharmacokinetics and dose-dependently modulated leucocytes and cytokines. Compared with placebo at week 24, iberdomide 0.45 mg significantly (p<0.001) reduced B cells, including those expressing CD268 (TNFRSF13C) (−58.3%), and plasmacytoid dendritic cells (−73.9%), and increased Tregs (+104.9%) and interleukin 2 (IL-2) (+144.1%). Clinical efficacy was previously reported in patients with high IKZF3 expression and high type I interferon (IFN) signature at baseline and confirmed here in those with an especially high IFN signature. Iberdomide decreased the type I IFN gene signature only in patients with high expression at baseline (−81.5%; p<0.001) but decreased other gene signatures in all patients. Conclusion: Iberdomide significantly reduced activity of type I IFN and B cell pathways, and increased IL-2 and Tregs, suggesting a selective rebalancing of immune abnormalities in SLE. Clinical efficacy corresponded to reduction of the type I IFN gene signature. Trial registration number: NCT03161483 .